2018
DOI: 10.3343/alm.2018.38.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blaZ Gene and Performance of Phenotypic Tests to Detect Penicillinase in Staphylococcus aureus Isolates from Japan

Abstract: Guidelines recommend that clinical laboratories perform phenotypic tests (nitrocefin-based test and penicillin 10-U [P10] or 1-U [P1] zone edge tests) to detect penicillinase in Staphylococcus aureus isolates. This study aimed to assess the prevalence of blaZ encoding penicillinase and perform various phenotypic tests in S. aureus isolates from Japan. We prospectively collected 200 methicillin-susceptible S. aureus isolates from June 2015 to January 2016 and performed six phenotypic tests (nitrocefin-based tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…The presence of the bla Z gene did not influence production of β-lactamase alone [ 50 , 51 ]. Here, not all penicillin-resistant S. aureus isolates from food (45.5%) and clinical samples (52.8%) possessed bla Z gene.…”
Section: Main Textmentioning
confidence: 99%
“…The presence of the bla Z gene did not influence production of β-lactamase alone [ 50 , 51 ]. Here, not all penicillin-resistant S. aureus isolates from food (45.5%) and clinical samples (52.8%) possessed bla Z gene.…”
Section: Main Textmentioning
confidence: 99%
“…When observing antimicrobial resistance in a clinical scenario metagenomic sequencing and assembly of whole samples may not be desired due to cost or time constraints. Instead, it may be more interesting to narrow down the resistance to a few potential candidate plasmids responsible for the resistance, then to either validate it experimentally with PCR or adjust treatment ( 36 ). For demonstration purposes, we investigate a resistance qualification in Staphylococcus aureus , which is infamous for e.g., methicillin resistance ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results from the current study did not find TEM , while CTXM2 and SHV1 were found in low levels, and CTXM1 was found in 16.7% of samples. Another gene related to β-lactamases was blaZ6 , which was present in only one sample, although the frequency of this gene varies depending on the region; for example, in Japan, it has a frequency between 1% and 3% [ 36 ].…”
Section: Discussionmentioning
confidence: 99%